PENGEMBANGAN AGROWISATA KISUCI MENJADI AGROWISATA UNGGUL DENGAN PENERAPAN TEKNOLOGI EKOLOGI, ATRAKSI EDUWISATA, KONTEN PROMOSI MEDIA SOSIAL - Sakti, Essy Malays Sari; Marhalinda, Marhalinda; Supradaka, Supradaka (Jurnal Abdi Insani, 2024)
KISUCI (Cikeas River Climate Community) is a community group that focuses on environmental issues, especially on the preservation of the Cikeas River, climate change mitigation, advocacy and public awareness of Cipambuan Village, Babakan Madang District, Bogor Regency, West Java. Economically, the Cipambuan community depends on the agricultural sector. In this sector, the community has fluctuating work periods and generally the densest work period is during the planting and harvest seasons. Outside of that season, work intensity decreases drastically, so that in this season, farmers are vulnerable to seasonal unemployment. Low income in the agricultural sector and minimal farming profits have resulted in a lack of interest among the younger generation in becoming farmers. The potential of Cipambuan Village to become a tourist city is greatly felt by the community, but the limitations of community knowledge about the concept of Agrotourism and the potential for welfare are very minimal. The main objective of this PKM is to empower Partners so that it is expected to increase community income, especially unemployed youth, and make Cipambuan Village, Bogor a superior tourist village through the implementation of ecological technology, educational tourism attractions and promotional content through social media. The method of implementing the activities carried out is the Socialization Stage, Training Method, Technology Application, Mentoring and Evaluation. The results of the PKM activities show that partner members can create educational attraction programs, animation-based learning modules and promotional content are available through social media and information boards. With the development of agrotourism, Cipambua Village becomes a tourist village and unemployed youth get jobs as tour guides